2014
DOI: 10.1002/embr.201338225
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic survey of mitochondria by ubiquitin

Abstract: Ubiquitin is a post-translational modifier with proteolytic and non-proteolytic roles in many biological processes. At mitochondria, it performs regulatory homeostatic functions and contributes to mitochondrial quality control. Ubiquitin is essential for mitochondrial fusion, regulates mitochondria-ER contacts, and participates in maternal mtDNA inheritance. Under stress, mitochondrial dysfunction induces ubiquitin-dependent responses that involve mitochondrial proteome remodeling and culminate in organelle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 167 publications
(280 reference statements)
0
44
0
Order By: Relevance
“…Consistently, several E3 ubiquitin ligases such as Mdm30, MITOL/MARCH-V, and MULAN (56) were found to associate with the cytosolic side of the OM. Likewise, the ubiquitin ligase Parkin is recruited to depolarized mitochondria (56,66,119,172,189,195). Additional mitochondria-associated modifiers like SUMO ligases have also been described (56).…”
Section: Outer Membrane Subproteomementioning
confidence: 99%
See 3 more Smart Citations
“…Consistently, several E3 ubiquitin ligases such as Mdm30, MITOL/MARCH-V, and MULAN (56) were found to associate with the cytosolic side of the OM. Likewise, the ubiquitin ligase Parkin is recruited to depolarized mitochondria (56,66,119,172,189,195). Additional mitochondria-associated modifiers like SUMO ligases have also been described (56).…”
Section: Outer Membrane Subproteomementioning
confidence: 99%
“…Mitochondrial fission serves to increase the number of mitochondria in the cell before mitochondrial biogenesis or cellular division, as well as to segregate dysfunctional or depolarized mitochondria away from the healthy network (144,178,196). Once malfunctioning (e.g., severely depolarized) mitochondria have been segregated, the components of their OM subproteome that are involved in establishing contact/tethering sites with other mitochondria are ubiquitylated and proteolyzed by UPS to prevent their rejoining with healthy mitochondria (56,66,172,189). Then, damaged organelles are removed via another facet of organellar MQC (Fig.…”
Section: Overview Of Mitochondrial Protein Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Because Okreglak and Walter (3) found that a number of mistargeted tailanchored proteins are not degraded via Msp1, the presence of additional pathways that facilitate the degradation of mislocalized tailanchored proteins is likely. Several pathways for ubiquitylation of mitochondrial outer membrane proteins and the recruitment of Cdc48 to the mitochondria have been described (19,20), which may contribute to the removal of mistargeted tail-anchored proteins from the mitochondria.…”
mentioning
confidence: 99%